Wound Healing Effect of Conditioned Media Obtained From Adipose Tissue on Human Skin Cells: A Comparative in Vitro Study. Issue 2 (August 2016) - Kober, Johanna; Gugerell, Alfred; Schmid, Melanie; Zeyda, Maximilian; Buchberger, Elisabeth; Nickl, Stefanie; Hacker, Stefan; Ankersmit, Hendrik Jan; Keck, Maike
Abstract : Background: Split-thickness skin grafting is the gold standard to cover extensive acute and chronic wounds with a well-vascularized wound bed. Although some headway has been made in developing biological agents to speed up healing, there is still no treatment that sufficiently replaces skin grafts to date. The use of secretory factors of adipose tissue may be a feasible approach to developing topical wound applications for faster wound healing. Methods: In this study, the effect of conditioned media (CMs) of human adipose-derived stem cells (ASCs), adipocytes, or adipose tissue on human skin cells was evaluated for viability, proliferation, and migration in vitro. Differentiation potential of stem cells treated with CM was monitored by AdipoRed staining and qualitative real-time polymerase chain reaction. Angiogenic potential of human endothelial cells treated with CM was tested via sprouting assay. Results: The CM of adipose tissue significantly enhanced ASC proliferation ( P < 0.01). Treatment with CM showed no inductive effect on ASC differentiation into adipocytes but, at the same time, significantly induced cell sprouting of endothelial cells ( P < 0.001). We show for the first time that CM of adipose tissue is a potent inducer of proliferation of ASCs and angiogenesis, with comparable effects with those of stem cell-enriched CM. Conclusions: We suggest the use of the secretome of adipose tissue to produce CM for topical application on wounds, rather than working with adipose tissue or including the difficult process of enriching the patients' stem cells in vitro.